Designing the Packaging of “Kue Sagon Kelapa” as a Promotional Medium for Mrs. Endulita’s MSME - Dwi Sulastri, Eko Agung (Indonesian Journal of Visual Culture, Design, and Cinema, 2025)
Abstract: This final project proposal is entitled "Designing Packaging for Coconut Sagon Cake as a Medium for Preserving Javanese Culinary Culture." This project aims to preserve the culinary heritage of Central Java, which is characterized by its distinctive flavors and significant cultural value. However, the lack of innovation in packaging design has led to limited product appeal, particularly in modern markets.In response to this issue, this research seeks to develop coconut sagon cake packaging that not only serves as a protective medium for the product but also functions as an effective promotional and educational tool.Based on these considerations, the proposed design will encompass unit packaging, inner box packaging, master box packaging, and special/thematic packaging. Through this initiative, it is expected that the packaging design will contribute to the preservation of traditional culinary heritage, enhance the product's brand identity, and increase public interest in locally produced . Keywords: packaging design, coconut sagon cake, promotion, education, traditional cuisine.